Technique development for regulating the rate of solenoidal magnetic field decrease - Reshetnyak, N.G.; Romas'ko, V.P.; Chertishchev, I.A. (Вопросы атомной науки и техники, 2016)
The problem of regulating the gradient of the solenoidal magnetic field decrease has been investigated in a wide range of values. The results of developing two methods of regulation are reported. With the first method, the field decrease of the main solenoid is regulated through the use of the stray magnetic field, which was produced by SmCО₅ permanent magnets. According to the second method, the regulation was realized with the use of an additional solenoid. The rate of field decrease was regulated within 50…400 Oe/cm. The electron beam formed by the magnetron gun was transported in the decreasing magnetic field of the solenoid. Measuring systems have been created to investigate the beam current distribution in the radial direction. Рассматривалась задача регулировки градиента спада магнитного поля соленоида в широком интервале значений. Приведены результаты разработки двух методов регулировки. В первом из них для регулировки спада поля основного соленоида использовано рассеянное магнитное поле, которое создавалось постоянными магнитами из SmCО₅. Во втором методе регулировка осуществлялась с помощью дополнительного соленоида. Скорость спада регулировалась в пределах 50…400 Э/см. Транспортировка электронного пучка, формируемого магнетронной пушкой, осуществлялась в спадающем магнитном поле соленоида. Созданы измерительные системы для исследования распределения тока пучка в радиальном направлении. Розглядалася задача регулювання градієнта спаду магнітного поля соленоїда в широкому інтервалі значень. Наведено результати розробки двох методів регулювання. У першому з них для регулювання спаду поля основного соленоїда використано розсіяне магнітне поле, яке створювалося постійними магнітами з SmCО₅. У другому методі регулювання здійснювалося за допомогою додаткового соленоїда. Швидкість спаду регулювалася в межах 50...400 Е/см. Транспортування електронного пучка, який формується магнетронною гарматою, здійснювалося в спадаючому магнітному полі соленоїда. Створені вимірювальні системи для дослідження розподілу струму пучка в радіальному напрямку.